2017
DOI: 10.1002/kin.21140
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Rate Constants for H + Tetramethylsilane and H + Silane and Implications about Structure–Activity Relationships for Silanes

Abstract: The shock-tube technique has been used to investigate the reactions H + SiH 4 → H 2 + SiH 3 (R1) and H + Si(CH 3 ) 4 → Si(CH 3 ) 3 CH 2 + H 2 (R2) behind reflected shock waves. C 2 H 5 I was used as a thermal in situ source for H atoms. For reaction (R1), the experiments covered a temperature range of 1170-1251 K and for (R2) 1227-1320 K. In both cases, the pressures were near 1.5 bar. In these experiments, H atoms were monitored with atomic resonance absorption spectrometry. Fits to the H-atom temporal concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 68 publications
2
16
3
Order By: Relevance
“…The energy barrier obtained at the G4 level of theory from our work agrees well with their result. Rate constants obtained in these two works agree well with the experimental data in the literature 40 . Arthur et al 42 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The energy barrier obtained at the G4 level of theory from our work agrees well with their result. Rate constants obtained in these two works agree well with the experimental data in the literature 40 . Arthur et al 42 .…”
Section: Resultssupporting
confidence: 88%
“…Arrhenius plot of R1: Si(CH 3 ) 4 + H ⇌ Si(CH 2 )(CH 3 ) 3 + H 2 total rate constants. Blackline: theory (G4), present work; red line: theory (G4), Peukert et al 40 43 …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…To rationalize the findings reported in this work, the experimental data were supported by TST calculations. Since the G4 composite approach has been previously used for calculations of energy profiles of chemical processes, , TST calculations were based on molecular properties and energetics at the G4 level of theory. The rate constants for H abstractions were calculated using TST, as implemented in the KiSThelP code .…”
Section: Experiments and Theorymentioning
confidence: 99%
“…This was also shown in a recent H-ARAS (atomic resonance absorption spectrometry) shock-tube study from our laboratory, where we have investigated the reactions H + SiH 4 → H 2 + SiH 3 and H + Si(CH 3 ) 4 → H 2 + Si(CH 2 )(CH 3 ) 3 (SiH 4 , monosilane; Si(CH 3 ) 4 , tetramethylsilane). 8 It was found that Si(CH 3 ) 4 and neopentane (C(CH 3 ) 4 ), which is the analogous hydrocarbon to Si(CH 3 ) 4 , have similar reactivity toward H abstractions. On the other hand, SiH 9 This result is interesting in terms of possible reactivity analogies between silicon-organic molecules and corresponding hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%